Open access Monographs in the library supply chain - Stone, Graham (Septentrio Conference Series, 2018)
Watch the VIDEO. Recent European studies have shown that there are a growing number open access monograph publishers, many of which can be described as New University Presses (NUPs) or Academic-Led Publishing (ALP) initiatives, in addition to other small open access presses. The majority of these presses publish open access e-books and also print-on-demand copies for sale. Key studies have shown a positive impact on the usage and discovery of open access books. Despite this evidence, NUPs, ALPs and open access presses in general, have difficulty in accessing the library supply chain - the channels that library acquisition departments use to buy print and e-book content via approved library suppliers, such as Dawson, Askews, ProQuest and EBSCO. This was evidenced in a 2017 landscape report from Jisc, Changing publishing ecologies: A landscape study of new university presses and academic-led publishing. As part of the ALP interviews for the study Rupert Gatti of Open Book Publishers noted that it would be helpful to have a service that “looks at how to bring academic content into the catalogues and the digital learning environments of the universities and to allow universities to also relate back to the publisher, so that there is a flow of information going back both ways”. As such, the Jisc report made a number of recommendations, including best practice in metadata and support with distribution/dissemination. In order to take these recommendations further, Jisc held a community workshop in July 2018 to surface issues with key stakeholders for the following problem statement: “OA publishers have difficulty accessing the channels that library acquisition departments use to buy print and e-book content”. The workshop brought together experts from NUPs, ALPs, book suppliers and distributors, metadata suppliers, libraries and other experts in OA publishing to discuss the above statement. The core aim of the workshop was to allow the experts to share their experiences and knowledge in order to get a better understanding of the supply chain and to gain insight into the problem statement. These discussions highlighted four key areas, which the group agreed needed further development. These have been captured as a set of recommendations and suggestions for best practice. This paper will introduce the ideas behind the workshop, before detailing the outcomes of the discussion sessions, which featured four round table sessions led by a NUP, an ALP, a book supplier and a library. Finally the paper will outline the four areas surfaced in the roundtable sessions. These included two practical areas, the library supply chain and metadata and two aspirational areas, cultural change in the acquisition process and new forms of content.